Long noncoding RNA-EBIC promotes tumor cell invasion by binding to EZH2 and repressing E-cadherin in cervical cancer. - Ning-xia Sun; Chen Ye; Qian Zhao; Qing Zhang; Chen Xu; Shao-bing Wang; Zhi-jun Jin; Shu-han Sun; Fang Wang; Wen Li (PLoS ONE)
In recent years, long noncoding RNAs (lncRNAs) have been demonstrated to play key roles in tumorgenesis. However, the contributions of lncRNAs to cervical cancer (CC) remain largely unknown. In this study, differentially expressed lncRNAs and mRNAs in cervical cancer and paired peritumoral tissues were detected by transcriptome microarray analysis. We found 708 probe sets of lncRNAs increased and 836 probe sets decreased in CC tissues, while 1288 mRNA differential probe sets increased and 901 mRNA probe sets decreased. The results were validated by quantitative real-time polymerase chain reaction (qPCR). Then, we found a specific differentially expressed lncRNA can physically bind to enhancer of zeste homolog2 (EZH2) by using RNA immunoprecipitation. We termed it as EZH2-binding lncRNA in cervical cancer [lncRNA-EBIC]. Wound healing assays and Matrigel invasion assays were used to determine the function of this lncRNA by silencing it. We observed that the migration and invasion of cervical cancer cells in vitro were inhibited upon suppression of lncRNA-EBIC by siRNA. We also found that the association between lncRNA-EBIC and EZH2 was required for the repression of E-cadherin, which was a key molecular in the metastasis of cervical cancer. Conclusion: These results demonstrated that lncRNA-EBIC was an oncogenic lncRNA, which could promote tumor cell invasion in CC by binding to EZH2 and inhibiting E-cadherin expression.